The role of the sandprawn, Callichirus kraussi, as an ecosystem engineer in a temporarily open/closed Eastern Cape estuary, South Africa - Njozela, Cuma (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2013)
The role of the sandprawn, Callichirus (=Callianassa) kraussi (Stebbing), as an ecosystem engineer was assessed in the lower reach of the temporarily open/closed Kasouga Estuary situated along the Eastern Cape coastline of southern Africa over the period April 2010 to June 2011. The study comprised two distinct components, a field study and a caging experiment. The field study assessed the correlation between sand prawn densities and selected physico-chemical (organic content of the sediment and bioturbation) and biological (microphytobenthic algal concentrations and macrobenthic abundance and biomass) variables in 50 quadrants in the lower reach of the estuary. Densities of the sand prawn within the quadrants ranged from 0 to 156 ind mâ »Â² (mean = 37 ind mâ »Â²). There were no significant correlations between the densities of the sandprawn and the estimates of the organic content of the sediment and the abundance and biomass of the macrofauna (P > 0.05 in all cases). Numerical analyses failed to identify any effect of the sandprawn density on the macrofaunal community structure. The rate of bioturbation was, however, strongly correlated to the sand prawn density. Similarly, the microphytobenthic alga concentrations were significantly negatively correlated to the sand prawn densities ((P < 0.05). The absence of any distinct impact of the sandprawn on the macrobenthic community structure appeared to be related to their low densities in the lower reach of the estuary during the study. To better understand the role of the sandprawn as an ecosystem engineer, a caging experiment was conducted using inclusion and exclusion treatments (n= 5 for each treatment). Densities of the sandprawn in the inclusion treatments (80 ind mâ »Â²) were in the range of the natural densities within the estuary. The experiment was conducted over a period of 18 weeks in the lower reach of the estuary during summer. The presence of the sandprawn, C kraussi, contributed to a significant decrease in the microphytobenthic algal concentrations and the abundance and biomass of the macrofauna (P < 0.05 in all cases). The decrease in the microphytobenthic algal concentrations in the presence of the sandprawn appeared to be related to the res-suspension of the sediments (bioturbation) generated by the burrowing and feeding activities of the sandprawn. The observed decrease in macrofaunal abundances and biomass in the inclusion treatments appeared to be mediated by both the decreased food availability (mainly the microphytobenthic algae) and the burial of organisms within the sediments. Numerical analysis indicated that the sandprawn did, however, not contribute to a change in the species composition of the macrofauna. Results of the current study indicate that C.kraussi plays an important role in structuring the invertebrate community and energy flow within temporarily/open closed Kasouga Estuary.
Keywords: Estuarine biology -- South Africa -- Eastern Cape; Decapoda (Crustacea) -- South Africa -- Eastern Cape; Biotic communities -- South Africa -- Eastern Cape; Bioenergetics -- South Africa -- Eastern Cape; Shrimps -- South Africa -- Eastern Cape; Estuarine ecology -- South Africa -- Eastern Cape